2017
DOI: 10.1128/mcb.00248-17
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Oxygen-Sensing Prolyl Hydroxylase for Metformin-Associated Lactic Acidosis Treatment

Abstract: Metformin is one of the most widely used therapeutics for type 2 diabetes mellitus and also has anticancer and antiaging properties. However, it is known to induce metformin-associated lactic acidosis (MALA), a severe medical condition with poor prognosis, especially in individuals with renal dysfunction. Inhibition of prolyl hydroxylase (PHD) is known to activate the transcription factor hypoxiainducible factor (HIF) that increases lactate efflux as a result of enhanced glycolysis, but it also enhances glucon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Similar results were obtained upon oral administration of the HIF-P4H inhibitors REC2923 or roxadustat, and these effects could be advantageous e.g. in T2D patients suffering from metformin-associated lactic acidosis [60]. In addition, liver-specific HIF-P4H-3 deletion in mice was shown to improve insulin signaling and to counteract diabetes [5].…”
Section: Hypoxia Hifs and Hif-p4hs In Nonalcoholic Fatty Liver Diseasupporting
confidence: 58%
“…Similar results were obtained upon oral administration of the HIF-P4H inhibitors REC2923 or roxadustat, and these effects could be advantageous e.g. in T2D patients suffering from metformin-associated lactic acidosis [60]. In addition, liver-specific HIF-P4H-3 deletion in mice was shown to improve insulin signaling and to counteract diabetes [5].…”
Section: Hypoxia Hifs and Hif-p4hs In Nonalcoholic Fatty Liver Diseasupporting
confidence: 58%
“…PHD inhibition is potentially applicable for anemia (45, 46), ischemia‐reperfusion (4749), colitis (50, 51), sepsis (43, 52), lactic acidosis (53), and lung injury (13, 15), and several PHD inhibitors have been developed (30, 54). Several clinical trials of orally bioavailable PHD inhibitors are being conducted for anemia in patients with chronic kidney diseases (30, 45, 46).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study by Oyaizu-Toramaru et al investigated the use of targeting oxygen-sensing prolyl hydroxylase (PHD) in patients with metformin-induced lactic acidosis. They found that inhibiting PHD activates a transcription factor, known as hypoxia-inducible factor (HIF), which promotes lactate efflux and gluconeogenesis by using lactate as the substrate; these all lower circulating lactate levels [ 8 ]. Even though there are many more treatment options for lactic acidosis, IV hydration therapy was effective in this case.…”
Section: Discussionmentioning
confidence: 99%